EFFORTS TO IMPROVE STUDENTS LEARNING OUTCOMES THROUGH APPLYING OF EXPERIMENT METHOD IN THE MATERIALS LEARNING SCIENCE OF ESTABLISHMENT OF SOIL - Rahayu, Hani (Pedagogi, 2016)
This study to determine the extent of the increase in the understanding of students through experimental learning methods on establishment of soil materials in SDN 2 Cimahi.Â  The method which used in this study is a classroom action research which adapted Kemmis Taggart model with three cycles each cycle executed one action, which consists of planning, implementation, observation and reflection. The subjects consisted of 30 students of class V SDN 2 Cimahi second semester. The instruments which used ware learning outcomes questions, observation sheet, study documentation, and questionnaires. The results indicated that there is increasing learning process, students activities, and students goals of science learning. In the first cycle of the average value reached 68.33. In the second cycle increased with an average value of 73.66, and in the third cycle of heightened again with an average value of 80.00. This results showed that learning science through using experimental learning methods can enhance students' understanding.Keywords: natural science teaching, experiment method, understanding student learning